An evaluation of prosthetic status and treatment needs among institutionalized elderly individuals of Delhi, India - Nisha Yadav; Roma Yadav; Meetika Pahuja; Sanchit Pardhan; Sahiba Miglani; Tamanna Malik (Wolters Kluwer Medknow Publications, 2017)
Context: Oral health is essential for elderly person's general health and well-being. The most common oral problem in elderly is tooth loss which results due to periodontal diseases and caries. Prosthetic status is very important as it is related to dietary intake and maintaining nutritional status. Hence, to promote the oral health of the elderly, we need to know their prosthetic status and need. Aims: The aim of this study is to find the prosthetic status and need of 65-74 years old elderly residing in old age homes of Delhi, India. Settings and Design: A cross-sectional study was conducted among a total of 464 residents of 20 old age homes of Delhi, India. Material and Methods: Residents with age group of 64-75 were included in the study. The prosthetic status with treatment need was recorded using the World Health Organization Oral Health Assessment Form (1997). Statistical Analysis Used: Chi-square test and t-test were used to find significance of variables. P < 0.05 was considered significant. Results: Full removable dentures were worn by 7.30% of participants with predominance in upper arch, and one bridge was seen in 9.10% of participants with predominance in lower arch. Full removable denture was required in 25.20% of participants. Most of participants required multiunit prosthesis in both upper as well as lower arch (42.20% and 36.20%, respectively). Conclusion: The present study underlines a considerable need for dental treatment in elderly as the prosthetic status of participants was poor, and prosthetic needs were high.